THE RELATIONSHIP BETWEEN NOCTURNAL ENURESIS AND SPINA BIFIDA OCCULTA. A PROSPECTIVE STUDY AT THE DEPARTMENT OF UROLOGY AND KIDNEY TRANSPLANTATION, FOUNDATION UNIVERSITY MEDICAL COLLEGE/FAUJI FOUNDATION HOSPITAL, RAWALPINDI - MASOOD , A; KHAN , IZ; ZAHID , MM; FAROUK , K; ULLAH , K; AHMED , K (Biological and Clinical Sciences Research Journal, 2023)
Nocturnal enuresis (NE) and spina bifida occulta (SBO) are common problems in childhood. SBO is more prevalent in patients with NE than in the asymptomatic general population. SBO in patients with NE may be associated with worse symptoms and affect the response to treatment. The present study was carried out to document the frequency of SBO in patients with NE and to determine its effect on the response to treatment. This prospective study was conducted at the Department of Urology and Kidney Transplantation, Foundation University Medical College/Fauji Foundation Hospital, Rawalpindi, from 24 August 2022 to 23 March 2023. Pediatric patients aged 6-15 years with NE were included in the study. A plain X-ray KUB, among other investigations, was performed to look for SBO. Patients were divided into two groups based on SBO. The severity of symptoms, treatment response, and other variables were recorded on proforma. All patients were treated with behavioral therapy and Imipramine 25mg. The response was assessed by a reduction in the number of wet nights at 3 months of treatment. Data were analyzed using SPSS version 21. Percentages and frequencies were given; mean ± SD was used for quantitative data. For the comparison of two categorical variables, the Chi-Square test was used. A total of 78 patients (51 boys and 27 girls), aged 6-15 years, and a mean age of 10.7 ± 2.8 years with nocturnal enuresis were included in the study. SBO was detected in 28.2% of children. SBO was most commonly seen at L5-S1 and S1 levels (31.8%). Patients with SBO had more severe symptoms and responded poorly to treatment. A complete response to treatment was observed in 66% of patients in the non-SBO group and only 22.7% in the SBO group. No response was seen in 8.9% of children in the SBO group and 27.2% in the SBO group. The difference in response to treatment in both groups was statistically significant (P=0.001) SBO is a frequent finding in patients with NE. It may be associated with more severe symptoms and adversely affect the treatment response.